SoulCycle : reputation management strategies in response to controversy - Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
In August 2019, billionaire Stephen Ross hosted a fundraiser luncheon for President Donald Trump. Ross owned a minority interest in SoulCycle, and this news sparked calls for boycotts against the fitness company. Customers responded, and the company experienced notable declines in attendance. SoulCycle studios located in the liberal locales of Los Angeles, New York City, and San Francisco represented almost half of the company's attendance and had the largest decreases. The fundraiser news and boycotts affected the reputation of SoulCycle and prompted company leaders to employ reputation management strategies to counter the negative narrative. This case study asks readers to review the details of the news story and identify ways for SoulCycle leaders to improve the reputation of the company and restore faith with their customers.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; SoulCycle; Corporate image -- Case studies; Branding (Marketing) -- Case studies; Public opinion -- Case studies